On the origin of evolution tracing 'Darwin's dangerous idea' from Aristotle to DNA - Gribbin, John, 1946- (Prometheus Books, 2022)
"The theory of evolution by natural selection did not spring fully formed and unprecedented from the brain of Charles Darwin. The idea of evolution had been around, in various guises, since the time of Ancient Greece. And nor did theorizing about evolution stop with what Daniel Dennett called "Darwin's dangerous idea." In this riveting new book, bestselling science writers John and Mary Gribbin explore the history of the idea of evolution, showing how Darwin's theory built on what went before and how it was developed in the twentieth century, through an understanding of genetics and the biochemical basis of evolution, into the so-called "modern synthesis" and beyond. Darwin deserves his recognition as the primary proponent of the idea of natural selection, but as the authors show, his contribution was one link in a chain that extends back into antiquity and is still being forged today"--